2018
DOI: 10.1007/s10935-018-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Familias Unidas for Health and Wellness: Adapting an Evidence-Based Substance Use and Sexual Risk Behavior Intervention for Obesity Prevention in Hispanic Adolescents

Abstract: We describe the adaptation of Familias Unidas, an evidence-based substance use and sexual risk behavior intervention, for obesity prevention in Hispanic adolescents. Intervention developers and experts in pediatric obesity, exercise physiology, dietetics, and the local parks system provided input for changes. Hispanic families also provided input through a series of 21 focus groups conducted before, during, and after an initial pilot test of the adapted intervention. After transcribing audiotaped sessions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This study used an RCT design to evaluate the relative efficacy of FUHW among a sample of 280 Hispanic overweight and obese adolescents and their primary caregivers compared with prevention as usual. 28 Study staff recruited participants beginning in 2015. Adolescents and their primary caregiver were eligible to participate in the study if the Hispanic adolescent: (1) was a student in the 7th/8th grade, (2) had a BMI ≥85th percentile adjusted for age and sex, (3) lived with an adult primary caregiver willing to participate in the 2-year study, and (4) had plans to remain a resident of the geographic study catchment area (i.e., South Florida) during the study period.…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…This study used an RCT design to evaluate the relative efficacy of FUHW among a sample of 280 Hispanic overweight and obese adolescents and their primary caregivers compared with prevention as usual. 28 Study staff recruited participants beginning in 2015. Adolescents and their primary caregiver were eligible to participate in the study if the Hispanic adolescent: (1) was a student in the 7th/8th grade, (2) had a BMI ≥85th percentile adjusted for age and sex, (3) lived with an adult primary caregiver willing to participate in the 2-year study, and (4) had plans to remain a resident of the geographic study catchment area (i.e., South Florida) during the study period.…”
Section: Study Samplementioning
confidence: 99%
“…The process of adapting Familias Unidas, an intervention targeted toward reducing substance use and sexual risk behaviors, to target obesogenic behaviors has been described in detail elsewhere. 28 The adapted intervention, FUHW, was developed with the input from experts in pediatric obesity, exercise physiology, dietetics, and nutrition, such that these experts provided intervention modifications aligned with existing evidence-based physical activity curriculums. The research team also adapted the intervention through an iterative process based on input from Hispanic adolescents and parents who participated in a series of focus groups conducted before, during, and after an initial pilot test of the adapted intervention.…”
Section: Interventionmentioning
confidence: 99%
“…A recent review of barriers and facilitators to initial and continued attendance in community-based lifestyle programs for overweight and obese youth concluded that a family-centered approach (where both parents and youth attend sessions), practical sessions (e.g., hands on cooking activities and physical activity), and social interaction and support were important factors influencing continued attendance [ 67 ]. All of these characteristics are central to the present intervention and were previously endorsed by those participating in the initial pilot/feasibility study as important features of the program [ 45 ]. Specifically, parents described feeling engaged by intervention content and social connections, reported enjoying hands-on nutrition training activities, perceived improvements in family cohesion, and described the intervention social climate as being very positive.…”
Section: Discussionmentioning
confidence: 99%
“…Familias Unidas for Health and Wellness was adapted from an evidence-based intervention for Hispanic adolescents (“Familias Unidas”) shown to be efficacious and effective in preventing and reducing substance use and sexual risk behaviors in Hispanic adolescents across four randomized controlled trials [ 49 , 50 , 51 ]. The adaptation process is described in detail elsewhere [ 45 ]. Briefly, intervention developers and experts in pediatric obesity, exercise physiology, dietetics, and the local parks system provided input for changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation